Some Recent Tendencies in the Development of the Foreign Trade of the United States - Roorbach, G. B. (The Review of Economics and Statistics, 1920)
T HE unusual interest now taken in the development of the foreign trade of the United States is, to a considerable extent, due to the changes in international commerce brought about by the Great War. The new markets for American goods that have been made available, the change of the United States from a debtor to a creditor nation, the increasing demands for foreign raw materials for an expanding industrial life in the United States, the resulting problems of credits, of financing trade, and of the relation of tariff policies to the new conditions all these and other considerations are focusing attention to foreign trade and foreign trade problems to an extent never before experienced in this country. The student of foreign trade who is attempting to look into the future of our trade development is constantly asking the questions: To what extent are the present conditions in trade a result of abnormal circumstances growing out of.the war, and to what extent do they represent the working out of tendencies that were already manifest during the. period preceding the war ? Which of the changes are temporary, which represent permanent adjustments to conditions that were already thanging before the war brought in the complications ? Final answers to these questions cannot be given at the present time, but an analysis of our foreign trade during the years preceding the summer of I914, combined with certain facts and tendencies of trade development since then, even if it does not show the exact path that will be followed may be very helpful in indicating the direction in which our trade is moving. The purpose of this article is: